Biological Properties of Boletus edulis Extract on Caco-2 Cells: Antioxidant, Anticancer, and Anti-Inflammatory Effects - Javier Quero; Mónica Paesa; Carmen Morales; Gracia Mendoza; Jesús Osada; José António Teixeira; Pedro Ferreira-Santos; María Jesús Rodríguez-Yoldi (MDPI AG, 2024)
Boletus edulis (BE) is a mushroom well known for its taste, nutritional value, and medicinal properties. The objective of this work was to study the biological effects of BE extracts on human colon carcinoma cells (Caco-2), evaluating parameters related to oxidative stress and inflammation. In this study, a hydroethanolic extract of BE was obtained by ohmic heating green technology. The obtained BE extracts are mainly composed of sugars (mainly trehalose), phenolic compounds (taxifolin, rutin, and ellagic acid), and minerals (K, P, Mg, Na, Ca, Zn, Se, etc.). The results showed that BE extracts were able to reduce cancer cell proliferation by the induction of cell cycle arrest at the G0/G1 stage, as well as cell death by autophagy and apoptosis, the alteration of mitochondrial membrane potential, and caspase-3 activation. The extracts modified the redox balance of the cell by increasing the ROS levels associated with a decrease in the thioredoxin reductase activity. Similarly, BE extracts attenuated Caco-2 inflammation by reducing both iNOS and COX-2 mRNA expression and COX-2 protein expression. In addition, BE extracts protected the intestine from the oxidative stress induced by H2O2. Therefore, this study provides information on the potential use of BE bioactive compounds as anticancer therapeutic agents and as functional ingredients to prevent oxidative stress in the intestinal barrier.